2012
DOI: 10.1088/1752-7155/6/2/026001
|View full text |Cite
|
Sign up to set email alerts
|

Profile of eicosanoids in breath condensate in asthma and COPD

Abstract: The collection of exhaled breath condensates (EBC) is a noninvasive method for obtaining samples from the lungs. Eicosanoids are lipid mediators implicated in the asthmatic inflammatory response. The objective of our study was to investigate whether the profile of eicosanoid lipid mediators in EBC can characterize the inflammation in asthma and chronic obstructive pulmonary disease (COPD). EBC samples were collected from 22 healthy controls (C), 25 mild intermittent asthmatics (MIA), 20 with moderate to severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…Caffeic acid is also a potent inhibitor of 5-LO (26), which is upregulated in COPD patients (21,27). Indole compounds also have antioxidant properties and have been developed as MPO inhibitors (34).…”
Section: L168 Inhibitors Of Acute Cigarette Smoke-induced Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Caffeic acid is also a potent inhibitor of 5-LO (26), which is upregulated in COPD patients (21,27). Indole compounds also have antioxidant properties and have been developed as MPO inhibitors (34).…”
Section: L168 Inhibitors Of Acute Cigarette Smoke-induced Inflammationmentioning
confidence: 99%
“…Cysteinyl leukotrienes are potent bronchoconstrictors and also act to increase vascular permeability to cause edema and enhance mucus secretion (36). Leukotriene B 4 , a neutrophil chemoattractant and activator, is increased in exhaled breath condensate from COPD patients (21,27). Inhibitors of the leukotriene pathway were found somewhat effective in several clinical trials in COPD (20,54).…”
mentioning
confidence: 99%
“…Recently, Wang et al [20] have reported that sEH-selective inhibitors, which stabilize EETs by preventing their conversion to DHETs, have significant protective effects on tobacco smoke-induced lung injury in a rat model of COPD. Furthermore, the concentrations of 11,12-EET are higher the exhaled breath condensates of patients with COPD than those of control subjects, while the concentrations of 8,9-EET are lower in COPD patients [21] Although these observations imply that EETs may play an important role in the pathogenesis of COPD, the precise mechanisms of EETs protecting against COPD are still unclear.…”
Section: Introductionmentioning
confidence: 96%
“…This may be attributable to between-study methodological differences, however, three studies (18,21,35) made within-study comparisons of severity. Samitas et al (18) report a significant difference between the severe and milder asthma groups, whereas…”
Section: Figure 4 -Mean 8-isoprostane and Standard Deviation: Asthma mentioning
confidence: 99%